Preparation, Characterization And Activity Evaluation Of Multi-Component Photocatalyst Under Visible Light Irradiation - Nor Amalina, Hussain (2012)
The aim of the present work is to synthesize and characterize P-type, N-type and P-N type photocatalysts for wastewater treatment, to compare photocatalytic activity of different catalysts for dye degradation and to study the effect of visible light irradiation of difference parameter of photocatalytic reaction. Multicomponent P-type and P-N type photocatalyst were synthesized and characterized by XRD, SEM and BET. The visible light is used to study the catalyst activity for the composition of dye using photocatalyst. However, the photocatalytic activity under visible light is low. In order to increase its activity, multi-component photocatalyst is used. P-N-type semiconductor is used as the photocatalysts as it improve the photocatalytic activity using couple catalyst by accelerating the separation of electron-hole pair as well as to efficiently extend the region of visible light utilization. This research will demonstrated the feasibilities of the photocatalytic degradation of Methylene Blue for treating wastewaters where it is depends by varying the initial concentrations of Methylene Blue, addition amounts of P-type photocatalyst and the light irradiation. As a result, the photocatalytic activity followed the series of CaFe2O4-V2O5 >> CaFe2O4-WO3 > CaFe2O4. Based on the findings of this study, some recommendation can be made which are calcinations of the catalyst with different temperature, effect of visible light power intensity and effect of different dopants and their characterization by XRD and XPS.